A plant pathogenic bacterium exploits the tricarboxylic acid cycle metabolic pathway of its insect vector. Issue 1 (1st January 2018) - Killiny, Nabil; Nehela, Yasser; Hijaz, Faraj; Vincent, Christopher I.
ABSTRACT: Huanglongbing in citrus is caused by a phloem-limited, uncultivable, gram-negative α-proteobacterium, Candidatus Liberibacter asiaticus ( C Las). C Las is transmitted by the phloem-sucking insect, Diaphorina citri (Hemiptera: Liviidae), in a persistent, circulative, and propagative manner. In this study, we investigated the metabolomic and respiration rates changes in D. citri upon infection with C Las using gas chromatography-mass spectrometry (GC-MS) and gas exchange analysis. The level of glycine, L -serine, L -threonine, and gamma-amino butyric acid were higher in C Las-infected D. citri, whileL -proline, L -aspartic acid, andL -pyroglutamic acid were lower in C Las-infected D. citri compared with the control. Citric acid was increased in C Las-infected D. citri, whereas malic and succinic acids were reduced. Interestingly, most of the reduced metabolites such as malate, succinate, aspartate, andL -proline are required for the growth of C Las. The increase in citric acid, serine, and glycine indicated that C Las induced glycolysis and the tricarboxylic acid cycle (TCA) in its vector. In agreement with the GC-MS results, the gene expression results also indicated that glycolysis and TCA were induced in C Las-infected D. citri and this was accompanied with an increases in respiration rate. Phosphoric acid and most of the sugar alcohols were higher in C Las-infected D. citri, indicating a response to the biotic stress or cell damage. Only slight increases in the levels of few sugars were observed in C Las-infected D. citri, which indicated that sugars are tightly regulated by D. citri . Our results indicated that C Las induces nutrient and energetic stress in its host insect. This study may provide some insights into the mechanism of colonization of C Las in its vector.